2012
DOI: 10.1007/s10608-012-9455-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Positive Schemas in Child Psychopathology and Resilience

Abstract: Research on child psychopathology focuses almost exclusively on the role of negative schémas as a vulnerability factor, while there has been a neglect of research on the role ofpositive schémas in child psychopathology (MacLeod & Moore, 2000). While decades of research have established negative cognitive schémas as a potent vulnerability factor for various negative developmental outcomes (e.g., Abela & Hankin, 2008), cognitive models of child psychopathology have yet to fully integrate positive schémas as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 118 publications
(173 reference statements)
6
60
0
4
Order By: Relevance
“…Gencoz and colleagues (2001) found that a lack of positive schema content in a sample of 9 to 17 year-olds was a specific cognitive feature of depression, rather than other internalizing disorders (i.e., anxiety). Most recently, in a sample of 170 adolescents aged 9 to 14, positive schema content was negatively related to depression and importantly, explained more variance in youth depressive symptoms than negative schema content (Keyfitz et al, 2012). In particular, these results suggest that the absence of positive schemas may be a particularly important predictor of depressive symptoms among youth (Keyfitz et al, 2012).…”
Section: Positive Schemas and Depressionmentioning
confidence: 85%
See 4 more Smart Citations
“…Gencoz and colleagues (2001) found that a lack of positive schema content in a sample of 9 to 17 year-olds was a specific cognitive feature of depression, rather than other internalizing disorders (i.e., anxiety). Most recently, in a sample of 170 adolescents aged 9 to 14, positive schema content was negatively related to depression and importantly, explained more variance in youth depressive symptoms than negative schema content (Keyfitz et al, 2012). In particular, these results suggest that the absence of positive schemas may be a particularly important predictor of depressive symptoms among youth (Keyfitz et al, 2012).…”
Section: Positive Schemas and Depressionmentioning
confidence: 85%
“…Similar to previous studies (e.g., Keyfitz et al, 2012), this study conceptualized resilience as self-reported capacity to cope or effectively manage self-appraised life difficulties (e.g., health problems) or stressful life events (e.g., death of a family member) adaptively. It is important to note that resilience is considered an ordinary developmental process that stems from normative human resources rather than unusual or extraordinary qualities (Masten, 2001).…”
Section: Cognitive Schemas and Resiliencementioning
confidence: 89%
See 3 more Smart Citations